Process-Oriented Smart Adsorbents: Tailoring the Properties Dynamically as Demanded by Adsorption/Desorption - Jiang, Yao; Tan, Peng; Liu, Xiao-Qin; Sun, Lin-Bing (Accounts of chemical research, 2022)
Conspectus Adsorptive separation plays a critical role in chemical, food, pharmaceutical, and environmental industries, as well as in many other industrial areas. Adsorbents are most important for adsorptive separation and undergo adsorption and desorption processes to accomplish the specific tasks of separation. In the process of adsorption, adsorbates diffuse into the pore spaces of adsorbents through pore openings, adsorb on active sites via physical or chemical interactions, and subsequently are regenerated by temperature or pressure swings during desorption. In the process of adsorption and desorption, however, the requirements for pore structures and surface properties of adsorbents are different. In general, adsorbents with small pore openings can realize selective adsorption and do not favor desorption; on the other hand, adsorbents with large pore openings are efficient in desorption but at the expense of adsorption selectivity. Remarkably, active sites possessing strong interactions with adsorbates contribute to high selectivity for adsorption, while desorption becomes difficult. The trade-off between adsorption and desorption presents an enormous challenge to develop high-efficiency adsorbents. Restricted by their fixed structures and surface properties, conventional adsorbents are unable to meet the demands of adsorption and desorption processes simultaneously. To confront the obstacles, the development of advanced adsorbents to meet the demand of adsorptive separation are urgent. A key strategy to address such issues lies in dynamically adjusting the pore structures or the surface properties of adsorbents with controllability according to the demands of adsorption/desorption. For instance, pursuant to the requirements of varying pore structures during adsorption/desorption, the pore openings of adsorbents can be customized through dynamic structural change of the decorated stimuli-sensitive motifs by suitable external intervention. In addition, the active sites within the adsorbents can be exposed to enhance the adsorption selectivity or sheltered to accelerate the desorption through stimuli-triggered adsorbent–adsorbate interactions. Hence, we proposed a concept of process-oriented smart adsorbents (POSAs) on the basis of the requirements of the adsorption/desorption processes. The design and development of such POSAs are based on three aspects, namely, pore openings, pore spaces, and adsorption sites of adsorbents. In this Account, we present the progress in the development of POSAs according to the demands of adsorption/desorption processes. A series of POSAs with incorporated stimuli-sensitive motifs were successfully achieved. The versatility of incorporated motifs allows them to tune the pore structures and surface properties of adsorbents dynamically and further to enhance the adsorption and desorption efficiency simultaneously. Based on the concept of POSAs, we hope that this Account could contribute to the development of high-efficiency adsorbents and ultimately promote their applications in practical industrial separation. Moreover, we present an outlook on future trends and challenges on the road toward the development and applications of POSAs.